Thrombophilic Risk Factors in Patients With Inflammatory Bowel Disease - Yazici, Ayten (Gastroenterology Res, 2010)
BACKGROUND: Inflammatory bowel disease (IBD) patients have an increased risk for thromboembolism. The aim of this study was to assess the presence of thrombophilic risk factors in IBD patients and to assess the associations of these factors with disease activity. METHODS: Forty-eight patients with IBD (24 ulcerative colitis, 24 Crohn’s disease) and 40 matched healthy control individuals were enrolled. In addition to routine biochemical analysis, fasting blood samples were studied for prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen, protein-C, protein-S, antithrombin III, factor VII, factor VIII, D-dimer, vitamin B(12), folic acid and homocysteine. RESULTS: Levels of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), fibrinogen, D-dimer and the number of platelets were significantly higher in patients with IBD. When compared to control group, in patients with Crohn’s disease serum homocystein levels were significantly higher (p = 0.025) while serum folic acid levels were significantly lower (p < 0.019). Levels of fibrinogen, D-dimer, protein C, factor VIII, total homocystein and the number of platelets were found to be significantly higher in Crohn’s disease patients who were in active period of the disease. CONCLUSIONS: Thrombophilic defects are multifactorial and might be frequently seen in IBD patients. They might contribute to thrombotic complications of this disease.